Second round results from the Manchester 'Lung Health Check' community-based targeted lung cancer screening pilot. Issue 7 (12th November 2018) - Crosbie, Phil A; Balata, Haval; Evison, Matthew; Atack, Melanie; Bayliss-Brideaux, Val; Colligan, Denis; Duerden, Rebecca; Eaglesfield, Josephine; Edwards, Timothy; Elton, Peter; Foster, Julie; Greaves, Melanie; et al.
Abstract : We report results from the second annual screening round (T1) of Manchester's 'Lung Health Check' pilot of community-based lung cancer screening in deprived areas (undertaken June to August 2017). Screening adherence was 90% (n=1194/1323): 92% of CT scans were classified negative, 6% indeterminate and 2.5% positive; there were no interval cancers. Lung cancer incidence was 1.6% (n=19), 79% stage I, treatments included surgery (42%, n=9), stereotactic ablative radiotherapy (26%, n=5) and radical radiotherapy (5%, n=1). False-positive rate was 34.5% (n=10/29), representing 0.8% of T1 participants (n=10/1194). Targeted community-based lung cancer screening promotes high screening adherence and detects high rates of early stage lung cancer.